A Privacy Preservation Secure Cross Layer Protocol Design for IoT Based Wireless Body Area Networks Using ECDSA Framework. - Sharavanan, P. T.; Sridharan, D.; Kumar, R. (Journal of Medical Systems, 2018)
Internet of Things (IoT) provides the collection of devices in different applications in which Wireless Body Area Network (WBAN) is placed an crucial role. The WBAN is a wireless sensor network consisting of sensor nodes that is collected from IoT which is implanted in the human body to remotely monitor the patient’s physiological signals without affecting their routine work. During emergency situations or life-threatening situations there is a need for a better performance to deliver the actual data with an efficient transmission and there is still a challenge in efficient remote monitoring. So, in this paper an application for cross layer protocol design architecture of Elliptic Curve Digital Signature Algorithm (ECDSA) has been proposed. It replaces the protocol architecture of WBAN (IEEE 802.15.6), WMAN (IEEE 802.16), and 3G, WLAN (IEEE 802.11) or wired networks. The lightweight secure system provides secure data transmission and access control mechanisms by using ECDA-based proxy signature algorithm. The efficiency of the system is implemented using simulation models that were developed using NS-2, and the results obtained shows an optimum solution in terms of delay, PDR, throughput, jitter, packet transmission time, dropping ratio and packet delivery. The viability of the methodology proposed is illustrated by the response.